2006
DOI: 10.1152/ajpregu.00757.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to dexamethasone alters hippocampal drive on hypothalamic-pituitary-adrenal axis activity in adult male rats

Abstract: Glucocorticoids are essential for normal hypothalamic-pituitary-adrenal (HPA) axis activity; however, recent studies warn that exposure to excess endogenous or synthetic glucocorticoid during a specific period of prenatal development adversely affects HPA axis stability. We administered dexamethasone (DEX) to pregnant rats during the last week of gestation and investigated subsequent HPA axis regulation in adult male offspring in unrestrained and restraint-stressed conditions. With the use of real-time PCR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 62 publications
3
72
2
Order By: Relevance
“…A programmed increase in responsiveness of the rat adrenal to stress is in line with previous reports showing enhanced activity of the adult HPA axis at both the hypothalamic and pituitary levels after fetal glucocorticoid excess. Thus, Shoener et al (2006) reported elevated expression of hypothalamic CRH in adult offspring of dexamethasone-treated mothers, and perinatal dexamethasone treatment was shown to increase pituitary corticotroph number in female offspring ( John et al 2006). Our observation that adrenal Mc2r expression is elevated in offspring of dexamethasone-treated mothers suggests that an enhanced HPA reactivity also involves greater responsiveness at the level of the adrenal (i.e.…”
Section: Discussionmentioning
confidence: 63%
“…A programmed increase in responsiveness of the rat adrenal to stress is in line with previous reports showing enhanced activity of the adult HPA axis at both the hypothalamic and pituitary levels after fetal glucocorticoid excess. Thus, Shoener et al (2006) reported elevated expression of hypothalamic CRH in adult offspring of dexamethasone-treated mothers, and perinatal dexamethasone treatment was shown to increase pituitary corticotroph number in female offspring ( John et al 2006). Our observation that adrenal Mc2r expression is elevated in offspring of dexamethasone-treated mothers suggests that an enhanced HPA reactivity also involves greater responsiveness at the level of the adrenal (i.e.…”
Section: Discussionmentioning
confidence: 63%
“…In this model of LBW, we studied the effects of ESC treatment on insulin sensitivity and HPA axis activity in a rat model of LBW (17,64). This model has previously been shown to be insulin resistant and to have HPA axis hyperactivity, pituitary hyperplasia of the ACTH-producing cells, and increased ACTH secretion (17,64).…”
Section: Discussionmentioning
confidence: 99%
“…4). Whereas there is much information about the long-term effects of early-life glucocorticoids on levels of its two receptors in the hippocampus, GR [47,107,148] and mineralocorticoid receptor (MR;148,130), little is known about the effects of these hormones on either hippocampal CRH or the CRH receptor, CRF 1 . In adult rats, administration of the synthetic glucocorticoid hormone, dexamethasone, does not influence CRH levels in the hippocampus [32].…”
Section: Interactions Among Glucocorticoid-and Crh-mediated Mechanismsmentioning
confidence: 99%